Study of the Van der Pol Oscillator with Fractional Derivatives - Barbosa, Ramiro (2019)
In this paper we propose a modified version of the classical Van der Pol oscillator by introducing fractional-order time derivatives into the state-space model. The resulting fractional-order Van der Pol oscillator is analyzed in the time and frequency domains, by using phase portraits, spectral analysis and bifurcation diagrams. The fractional-order dynamics is illustrated through numerical simulations of the proposed schemes by using approximations to fractional-order operators. Finally, the analysis is extended to the forced Van der Pol oscillator.